Guilty Bonds - Le Queux, William, 1864-1927 (Salt Lake City, UT : Project Gutenberg, 2012)
"Guilty Bonds" by William Le Queux is a mystery novel written in the late 19th century. The story revolves around Frank Burgoyne, a young journalist who becomes embroiled in a series of enigmatic murders linked by a mysterious seal found on the victims. The narrative begins with Burgoyne's simple life turning chaotic after he discovers a woman murdered in a house, leading him to pursue a suspect and ultimately find himself drawn deeper into a web of intrigue and danger. The opening of the novel introduces Frank Burgoyne as he enjoys a casual evening with a friend, which quickly spirals into a night of horror when he witnesses a woman's brutal murder. He becomes a reluctant witness to a series of mysterious crimes that have left the police baffled. Despite his newfound wealth and the Bohemian lifestyle he cherishes, Frank$1 (Bs life is upended as he grapples with accusations of murder and the looming threat of a perpetrator who seems to taunt authorities. The stage is set for a suspenseful journey of self-discovery, peril, and the pursuit of justice as Frank must navigate the complex world he is now part of. (This is an automatically generated summary.)s
Release date is 2012-11-23
Produced by Nick Hodson of London, England
Keywords: Mystery fiction